2004
DOI: 10.1902/jop.2004.75.6.852
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of an Amine Fluoride/Stannous Fluoride and an Antimicrobial Host Protein Mouthrinse on Supragingival Plaque Regrowth

Abstract: Although the effect on plaque regrowth observed with 0.12% CHX rinsing was superior to that with ASF, the ASF rinse was not associated with side effects. These findings, together with those from long-term trials, suggest that the ASF rinse may represent an effective alternative to CHX rinse as an adjunct to oral hygiene. On the contrary, the LLL rinse did not significantly inhibit plaque regrowth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…In contrast, the plaque reduction was minimal for incisors, especially lower incisor and lingual surface. Similar finding was reported by Pizzo et al [ 35 , 36 ]. It may be argued that the lingual surfaces of lower incisors may not be adequate in evaluating the plaque reduction by the use of mouthrinse, since they are in close contact with the tip of tongue, which may influence the early plaque regrowth.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, the plaque reduction was minimal for incisors, especially lower incisor and lingual surface. Similar finding was reported by Pizzo et al [ 35 , 36 ]. It may be argued that the lingual surfaces of lower incisors may not be adequate in evaluating the plaque reduction by the use of mouthrinse, since they are in close contact with the tip of tongue, which may influence the early plaque regrowth.…”
Section: Discussionsupporting
confidence: 92%
“…Rinsing with 0.12% CHX alone during prolonged periods, but without professional regular debridement does not appear to reduce subgingival bacterial counts in subjects with periodontitis (Persson et al 2007). In comparison with CHX rinses, no other mouth rinses have shown superiority to control bacterial colonization or gingival inflammation (Moran et al 1992, Jenkins et al 1994, Renton‐Harper et al 1998, Pizzo et al 2004).…”
mentioning
confidence: 99%
“…However, an in vitro study showed that a lactoferrin-containing toothpaste did not show superior antibacterial effects compared to a toothpaste containing the anionic surfactant sodium lauryl sulfate (SLS) [ 38 ]. In addition, Pizzo et al could not find an inhibition of plaque regrowth by using a mouthwash with lactoferrin, lactoperoxidase, and lysozyme [ 39 ]. In patients with xerostomia, products with lactoferrin have been tested [ 40 , 41 , 42 ].…”
Section: Overview On Adjunct Ingredients Used In Hydroxyapatite-based...mentioning
confidence: 99%